Wife battering policies, programs and definitions: A social constructionist analysis. - McLean, Craig. (University of Ottawa (Canada), 1997)
This thesis examines the social definition process of the social problem of wife battering in Canada from 1970 to 1990. The primary component of the thesis is an examination of the development of various conceptual frameworks. The issue of wife battering would not have evolved as a social problem had it not been for the raised political consciousness of feminism and other social movements. The early efforts of the battered women's movement to gain recognition soon entered a stage characterized by co-optation, professionalism, and bureaucracy. Government and nongovernment officials, activists and academics played an ambivalent role in shaping the public definition of wife battering. On one hand these agencies and officials would occasionally provide financial support, legitimation, and credibility for the movement. On the other hand, these agencies and officials would compete against the movement for funding and for control of the social policy agenda. Literature on the battered women's movements in the United States of America and Great Britain are examined. An attempt was made to document and assess the various positions and perspectives of the various interest groups who were involved in the social construction of wife battering as a major social policy area. A number of divergent perspectives of frameworks were identified: the victims' position, the family violence perspective, the spousal abuse, wife battering and wife assault approaches. The social constructionist framework highlighted the existence of policy shifts and trends related to wife battering in Canada. (Abstract shortened by UMI.)
Keywords: History, Canadian.